Guru Profesional Abad XXI - Hasratuddin Hasratuddin (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2020)
Education through learning with heart is an effort to humanize humans. When human behavior today does not show like a caliph who maintains peace in life, such as having shortcuts which deemed appropriate, then the education and teaching system needs to be reformed. A learning model that forms an ability to think logically, critically, creatively, obediently or consistently and fosters self-confidence and character is student-centered learning which includes constructive, interactive and reflective stages.